Kryptousia macronema gen. nov., sp. nov. and kryptousia microlepis sp. nov., nostocalean cyanobacteria isolated from phyllospheres - Alvarenga, Danillo Oliveira; Andreote, Ana Paula Dini; Branco, Luis Henrique Zanini [UNESP]; Fiore, Marli Fatima (My University, 2017)
Tropical ecosystems worldwide host very diverse microbial communities, but are increasingly threatened by deforestation and climate change. Thus, characterization of biodiversity in these environments, and especially of microbial communities that show unique adaptations to their habitats, is a very urgent matter. Information about representatives of the phylum Cyanobacteria in tropical environments is scarce, even though they are fundamental primary producers that help other microbes to thrive in nutrient-depleted habitats, including phyllospheres. In order to increase our knowledge of cyanobacterial diversity, a study was conducted to characterize isolates from Avicennia schaueriana and Merostachys neesii leaves collected at a mangrove and an Atlantic forest reserve located at the littoral of São Paulo state, south-east Brazil. The morphological, ultrastructural, phylogenetic, molecular and ecological features of the strains led to the recognition of the new genus Kryptousia, comprising two new species, Kryptousia macronema gen. nov., sp. nov. and Kryptousia microlepis sp. nov., described here according to the International Code of Nomenclature for algae, fungi and plants. The new genus and species were classified in the nostocalean family Tolypotrichaceae. This finding advances knowledge on the microbial diversity of South American ecosystems and sheds further light on the systematics of cyanobacteria.
Keywords: Atlantic forest; Mangroves; Tolypotrichaceae; Tropical environments